PERANCANGAN HUMAN RESOURCE INFORMATION SYSTEM BERBASIS WEB DI PT THE MASTER STEEL - Aris Sunandar; Henri Septanto (Pusat Riset dan Inovasi Nasional, 2023)
Human Resource Information System is an important part of human resource management in modern organizations. In an effort to increase the efficiency and effectiveness of HRIS, many organizations are turning to web-based solutions. This study aims to design web-based HRIS using the Waterfall method as its development life cycle. The Waterfall method is a linear and sequential approach to software development. The stages in this method include needs analysis, design, implementation, testing, and maintenance. By using this method, it is possible to identify user needs, analyze and design system architecture, implement web-based Human Resource Information System solutions and test the system as a whole. The result of this research is a web-based Human Resource Information System that allows efficient management of employee information, personal data, attendance, payroll and performance evaluation. This Human Resource Information System also provides easy accessibility via a web browser, allowing users to access the system from anywhere and anytime.